PEMANFAATAN FERMENTASI TEPUNG MAGGOT (Hermetia illucens) SEBAGAI SUBSTITUSI TEPUNG IKAN DALAM PAKAN BUATAN UNTUK BENIH IKAN BAUNG (Hemibagrus nemurus) - Desenieli Harefa; Adelina Adelina; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted from December 10th, 2017 - February 10th, 2018 in Fish Nutrition Laboratory and Experimental Pond, University of Riau. The purpose of this research was to know the best percentage using fermented Maggot meal to substitute fish meal in diets on growth and feed efficiency of green catfish (Hemibagrus nemurus). This study used a Completely Randomized Design (CRD) with one faktor, five level treatments and three replications. Feeding trials was replacing fish meal with fermented maggot meal applied to P0 (0% fermented maggot meal), P1 (25% fermented maggot meal), P2 (50% fermented maggot meal), P3 (75% fermented maggot meal), and P4 (100% fermented maggot meal). The result showed that the best treatment contained in P3 (75% fermented maggot meal) with feed digestibility of 74,03%, feed efficiency of 73,38% and spesific growth rate of 4,12%. Keyword: Diets, Fermented Maggot meal, Green catfish (Hemibagrus nemurus), Growth, Substitution